BANCASSURANCE AS A MODERN ELEMENT OF FINANCIAL SECURITY - Петрик, Олександр; Дейсан, Ігор (Socio-economic relations in the digital society, 2019)
The article substantiates the concept of «bancassurance» as a modern component of financial security since the financial sector has been unstable for several years that negatively influence the relations between the banking and insurance sectors. Th e consequence of this cooperation — selling of insurance policies together with the products off ered by banks — is investigated. We should not forget about the customer who in one financial institution will acquire guaranteed excellence banking and insurance products. Interpretation of bancassurance in the modern market conditions is determined. An essential factor of banking and insurance cooperation — new distribution channels of insurance products — is discovered. The analysis of the bancassurance market in the developed countries of Europe is carried out. The examples of banking and insurance cooperation in the Polish finance market are considered. It was explored that in the developedcountries there is a signifi cant penetration of insurance companies into the market of banking services, as well as the information that, unlike in Ukraine, foreign banks receive a substantial part of their profi ts from the selling of insurance products. The leading companies on the Ukrainian market of insurance are noted. The peculiarities of activity and further development of bancassurance in Ukraine are determined. In the course of the study, it was found that in the insurancemarket of Ukraine, the dynamics of net insurance premiums and payments tend to increase. The number of insurance companies and banking institutions is decreasing. Th e deposit portfolio of banks is growing; but on the other hand, thecredit activity of banks remains rather low. Th is information denotes a close connection between the main performance indicators of banks and insurance companies. The main dominant areas of the development of banking insurance in  Ukraine are the creation of a space of trust in the insurance market and the formation of needs in insurance products from the population.
Keywords: banсassurance; financial security; bank; insurance company cooperation